STRATEGI PENGEMBANGAN KEAMANAN PRODUK IKAN TUNA (Thunnus albacares) DAN MAHI-MAHI (Coryphaena hippurus) BEKU UNTUK EKSPOR KE BERBAGAI NEGARA DI KAWASAN INDUSTRI MAKASSAR (KIMA) - Ardiana Amir; Andi Asni; Ernaningsih Ernaningsih (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2018)
Food safety is one of the requirements that become non-tariff barriers to enter the export market, mainly on the quality of products that do not meet quality standards set by the importing country. The purpose of this study is to analyze the causes and development of rejection of fishery products in the Makassar Industrial Area (KIMA) and the strategy of increasing the safety of frozen tuna and mahi-mahi products that are suitable for export to various export countries. The study was conducted on August 1 to September 30 2018 in the Makassar industrial area (KIMA). Using the Pareto diagram analysis method, causal analysis and SWOT Analysis. The results showed that during the years 2010-2017, six companies in the Makassar Industrial Area (KIMA) experienced cases of rejection caused by salmonella, filthy and histamine in 25 cases. The results of the priority analysis of fisheries product development strategies were based on the results of the analysis carried out. the best strategies in developing product development are as follows: (1) There is a need to provide comprehensive training on how to handle good catches for fishermen, suppliers by related agencies that are competent in their field; (2) Increased supervision of product quality processed by Quality Control (QC); (3) Companies must be able to review the causes of product rejection so that it does not recur from suppliers, every step of the process until delivery.